2021
DOI: 10.1038/s41598-021-87800-z
|View full text |Cite
|
Sign up to set email alerts
|

The combination of fluoxetine and environmental enrichment reduces postpartum stress-related behaviors through the oxytocinergic system and HPA axis in mice

Abstract: Gestational stress can increase postpartum depression in women. To treat maternal depression, fluoxetine (FLX) is most commonly prescribed. While FLX may be effective for the mother, at high doses it may have adverse effects on the fetus. As environmental enrichment (EE) can reduce maternal stress effects, we hypothesized that a subthreshold dose of FLX increases the impact of EE to reduce anxiety and depression-like behavior in postpartum dams exposed to gestational stress. We evaluated this hypothesis in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…As Both ketamine and uoxetine ameliorated anxiety-related behaviours, aligning with known anxiolytic effects (Houwing et al 2019;Carrier and Kabbaj 2013). The mechanism may involve buffering excess stimulation of the HPA axis and downstream corticosterone release triggered by maternal stress (Bashiri et al 2021). A rat model of in ammation-induced prenatal stress found that uoxetine prevented epigenetic effects on corticotrophin releasing factor receptor 2, which could mitigate anxiety by potentiating serotonin signalling (Bashiri et al 2021).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As Both ketamine and uoxetine ameliorated anxiety-related behaviours, aligning with known anxiolytic effects (Houwing et al 2019;Carrier and Kabbaj 2013). The mechanism may involve buffering excess stimulation of the HPA axis and downstream corticosterone release triggered by maternal stress (Bashiri et al 2021). A rat model of in ammation-induced prenatal stress found that uoxetine prevented epigenetic effects on corticotrophin releasing factor receptor 2, which could mitigate anxiety by potentiating serotonin signalling (Bashiri et al 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Cortisol crosses the placenta, directly impacting the offspring's developing HPA axis, predisposing them to affective disorders and cognitive de cits (Czarzasta et al 2019). Fluoxetine treatment during pregnancy prevents some HPA axis alterations by reducing corticosterone and ACTH levels while increasing oxytocin and vasopressin expression (Bashiri et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the results of this study, the AUC was 0.89, close to 0.9, so we think that saliva cortisol testing can be considered an auxiliary method for the clinical diagnosis of depression, and its diagnostic value is moderate. In addition, the collection of saliva cortisol in this study allows for non-invasive collection at regular intervals, which can be stably collected for several days before the experiment, so that the HPA axis in the free state can be effectively evaluated [ 68 , 69 ]. The assessment of cortisol in saliva has proven effective and reliable in reflecting the respective unbound hormones in the blood [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…between two animals was recorded as an index of social behaviour as previously described (Bashiri et al, 2021).…”
Section: Social Interaction Testmentioning
confidence: 99%